The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1371/journal.pone.0255772
|View full text |Cite
|
Sign up to set email alerts
|

Psychological preparedness for pandemic (COVID-19) management: Perceptions of nurses and nursing students in India

Abstract: Introduction The growing COVID-19 pandemic has posed a great threat to millions of people worldwide. Nurses and nursing students are an important group of health professionals who are most likely to face many challenges in this unprecedented scenario. The present study aimed at exploring nurses’ and nursing students’ perception of psychological preparedness for the pandemic (COVID-19) management. Materials & methods The study employed a quantitative cross-sectional online survey research design. Purposiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 13 publications
(18 reference statements)
5
14
0
Order By: Relevance
“…The findings can be regarded as reflecting nursing students’ personal resources, which are helpful in coping with adversity and support the optimum learning process. This claim was confirmed by the findings of Gandhi, which demonstrated a positive correlation between self-efficacy and optimism [ 73 ]. A high level of optimism has been demonstrated to contribute to a positive correlation with adaptation, it can improve an individual’s cognitive and emotional functioning when he/she is facing a challenge, or it can reduce the psychological stress level.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The findings can be regarded as reflecting nursing students’ personal resources, which are helpful in coping with adversity and support the optimum learning process. This claim was confirmed by the findings of Gandhi, which demonstrated a positive correlation between self-efficacy and optimism [ 73 ]. A high level of optimism has been demonstrated to contribute to a positive correlation with adaptation, it can improve an individual’s cognitive and emotional functioning when he/she is facing a challenge, or it can reduce the psychological stress level.…”
Section: Discussionsupporting
confidence: 67%
“…A high level of optimism has been demonstrated to contribute to a positive correlation with adaptation, it can improve an individual’s cognitive and emotional functioning when he/she is facing a challenge, or it can reduce the psychological stress level. Individuals with higher self-efficacy, optimism, and attentiveness are better mentally prepared to function during the pandemic [ 73 ]. Said et al confirmed that self-efficacy, self-esteem and dispositional optimism could be regarded as predictors for the evaluation of nurses’ psychological preparedness for disasters [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Swedish study among pediatric oncologists in 2009 showed that links were found between their level of optimism and experience, and their optimistic attitude was helpful for their resilience (Stenmarker et al., 2009). An Indian study among nurses performed during COVID‐19 pandemic indicated that psychological preparedness, self‐efficacy, resilience, and optimism were higher among the nursing faculty and administrators than the students, and it was explained by that the lack in these areas for the younger student might improve with age and work experience (Gandhi et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The participants assume that in the real-time situation in the hospitals, there are many supports given by their surroundings; hence, the participants feel safe and secure in undergoing their clinical rotation program. In this case, the sense of fear in the initial stage of undergoing a clinical rotation program can be overcome effectively by the participants [31].…”
Section: Discussionmentioning
confidence: 99%